Synthetic MRI derived relaxometry parameters: a new insight into characterization of ring enhancing lesions of brain - Dash, Sanket; Vyas, Sameer; Bhardwaj, Nidhi; Ahuja, Chirag Kamal; Modi, Manish; Chhabra, Rajesh; Sahu, Jitendra Kumar; Sankhyan, Naveen; Singh, Paramjeet (Neuroradiology, 2025)
Background and purpose Synthetic MRI utilizes the quantitative relaxometry parameters to generate multiple contrast images through a single acquisition. We tried to explore the utility of synthetic MRI derived relaxometry parameters in evaluation of ring enhancing lesions of brain. Materials and methods This was a prospective study. 40 subjects with ring enhancing lesions in brain underwent pre and post contrast synthetic MRI using MDME sequence. Pre and post contrast R1, R2 and PD values were recorded from the core, wall and perilesional edema of lesions and sub group analysis was done among infective, primary neoplastic and secondary neoplastic (metastatic) lesion groups. Results Pre and post contrast R1, R2 values from core were higher in the infective group compared to the others. Pre and post contrast R1, R2 values were lower in the wall where as it was significantly higher in the perilesional edema of primary neoplastic group. Post-pre the values increased significantly in the perilesional edema of primary neoplasms. R1 value of ≥ 0.689 and R2 value of ≥ 7.481 in the perilesional edema predicts a primary neoplasm over infection with 70.6% sensitivity and 85.7% specificity and over secondary neoplasm with 64.7% sensitivity and 100% specificity. Conclusion Synthetic MRI derived relaxometry parameters in ring enhancing lesions were found to be significantly different across sub groups and can be used to differentiate between primary neoplastic, secondary neoplastic and infective group with parameters from perilesional edema being the most useful.